Peristaltic locomotion without digital controllers: Exploiting multi-stability in origami to coordinate robotic motion. (October 2019) - Bhovad, Priyanka; Kaufmann, Joshua; Li, Suyi
Abstract: This study examines a novel approach to generate peristaltic-like locomotion in a segmented origami robot. Specifically, we demonstrate the use of multi-stability embedded in the origami skeleton to eliminate the need for multiple actuators or digital controllers to coordinate the complex robotic movements in peristaltic crawling. The crawling robot in this study consists of two serially connected bistable origami segments, each featuring a generalized Kresling design and a foldable anchoring mechanism. Mechanics analysis and experimental testing reveal that the nonlinear elastic behaviors of this dual-segment module, especially its rapid deformation due to the non-monotonic energy landscape and force–displacement relationship, can create a deterministic deformation sequence or actuation cycle. This cycle can then be used to generate the different phases in a peristaltic-like locomotion gait. Instead of individually controlling the segment deformation like in earthworm and other crawling robots, we only control the total length of this robot. Therefore, this approach can significantly reduce the total number of actuators needed for locomotion and simplify the control requirements. Moreover, the richness in Kresling origami design offers us substantial freedom to tailor the locomotion performance. The results of this study will contribute to a paradigm shift in how we can use the mechanics of multi-stability for robotic actuation and control.